Postharvest UV-C Treatment, Followed by Storage in a Continuous Low-Level Ethylene Atmosphere, Maintains the Quality of ‘Kensington Pride’ Mango Fruit Stored at 20 °C - Penta Pristijono; John B. Golding; Michael C. Bowyer (Horticulturae, 2018)
Mature green ‘Kensington Pride’ mangoes (Mangifera indica L.) were treated with a short-term UV-C light at four different intensities (0, 4.0, 8.3 and 11.7 kJ m−2). After treatment, mangoes were stored for 12 d in air (<0.005 μL L−1 ethylene) or 0.1 μL L−1 ethylene at 20 °C and 100% relative humidity (RH). Weight loss, peel colour, firmness, ethylene production, respiration rate, total soluble solids (TSS), titratable acidity (TA), total chlorophyll content, total phenolic content (TPC) and total antioxidant activity were assessed at 3-d intervals. The results showed that UV-C treatment delayed skin degreening, reduced endogenous ethylene production, suppressed respiration rate and lowered chlorophyll content compared to untreated control fruit. Fruit treated with UV-C had significantly higher TPC and total antioxidant activity at the end of the storage period than untreated fruits for both storage atmospheres. In addition, UV-C treated fruits remained significantly firmer than untreated fruits. UV-C treatment significantly affected TSS and TA levels in different ways. Storage of fruits in 0.1 μL L−1 ethylene significantly affected fruit firmness, respiration rate and ethylene production, while other fruit quality parameters were similar to fruit stored in air. These results indicated that UV-C irradiation could be used as an effective and rapid method to extend the postharvest life of mature green mangoes without adversely affecting certain quality attributes in the presence of low-level ethylene during storage.